5% Carbon Dioxide is safe but of limited efficacy as a treatment for paediatric non-convulsive status epilepticus: An open label observational study. (July 2016) - Forsyth, Rob; Martland, Tim; Lai, Ming; Vadlamani, Gayatri; Hogan, Vanessa
Abstract: Objective: To establish the efficacy and tolerability of inhaled 5% carbon dioxide/95% oxygen as a treatment for paediatric non-convulsive status epilepticus (NCSE). Methods: In an open label clinical trial, children in NCSE were given high flow inhaled 5% carbon dioxide/95% oxygen by face mask for 120 s under EEG control. Results: Six children (five male; ages 3–13; all with severe underlying epilepsy and disability) were recruited. Inhalation was well tolerated in all cases. Capillary blood gasses showed no significant derangements at the end of the inhalation. Effects on EEG normalisation were limited and transient, and no clinical improvements were noted. No adverse effects occurred. Conclusion: Inhaled 5% carbon dioxide/95% oxygen has been suggested as a potent, well tolerated anticonvulsant. An anticonvulsant without sedating and respiration-depressing effects would be particularly welcome in the management of NCSE where the justification for aggressive anticonvulsant therapy is often uncertain, however it appears that 5% carbon dioxide is of limited efficacy in this context. Highlights: Management of non-convulsive status epilepticus (NCSE) is under-researched. Sedaton is particularly disadvantageous in NCSE. Intracerebral pH manipulation has been suggested as a treatment for status epilepticus. Inhalation of 5% carbon dioxide was well-tolerated but not effective at terminating NCSE.